2019
DOI: 10.1002/hep.30131
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane X Receptor Regulates Liver Size and Liver Cell Fate by Yes‐Associated Protein Activation in Mice

Abstract: Activation of pregnane X receptor (PXR), a nuclear receptor that controls xenobiotic and endobiotic metabolism, is known to induce liver enlargement, but the molecular signals and the cell types responding to PXR-induced hepatomegaly remain unknown. In this study, the effect of PXR activation on liver enlargement and cell change was evaluated in several strains of genetically-modified mice and animal models. Lineage labelling using AAV-Tbg-Cre-treated Rosa26 mice or Sox9-Cre , Rosa26 mice was performed and Pxr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 50 publications
2
72
1
Order By: Relevance
“…The Hippo pathway is a highly conserved protein kinase cascade that has been proved to regulate cell fate, cell growth, tissue growth, tumorigenesis, and tumor metastasis (Guo et al, 2016;Yui et al, 2017;Oh et al, 2018). As the key downstream effector of hippo pathway, YAP1 has been demonstrated to have a close linkage with members of the nuclear receptor superfamily, such as FXR, PXR, and RXR (Anakk et al, 2013;Deng et al, 2019;Jiang et al, 2019). During cholestatic liver injury, multiple factors, such as BA (Gong et al, 2016) and endotoxemia (Hao et al, 2017), contribute to the activation of NLRP3 which represents a host defense to pathogens and damaging signals.…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo pathway is a highly conserved protein kinase cascade that has been proved to regulate cell fate, cell growth, tissue growth, tumorigenesis, and tumor metastasis (Guo et al, 2016;Yui et al, 2017;Oh et al, 2018). As the key downstream effector of hippo pathway, YAP1 has been demonstrated to have a close linkage with members of the nuclear receptor superfamily, such as FXR, PXR, and RXR (Anakk et al, 2013;Deng et al, 2019;Jiang et al, 2019). During cholestatic liver injury, multiple factors, such as BA (Gong et al, 2016) and endotoxemia (Hao et al, 2017), contribute to the activation of NLRP3 which represents a host defense to pathogens and damaging signals.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 (also known as interferon gamma–induced protein 10) not only activates and promotes inflammatory cells (e.g., macrophages) but also directly induces hepatocyte damage by targeting (C‐X‐C motif) chemokine receptor (CXCR3), resulting in liver injury and inflammation. TAZ, together with another transcriptional coactivator, yes‐associated protein (YAP), is the major downstream effector of the Hippo signaling pathway, playing an important role in promoting liver inflammation, regeneration, and carcinogenesis . Finally, in NASH patients, hepatic expression of Cxcl10 and Taz correlated well with expression of several potential miR‐223 targeted genes and inflammatory genes, suggesting that miR‐223 also plays an important role in ameliorating NASH by regulating Cxcl10 , Taz , and other targeted genes in NASH patients.…”
mentioning
confidence: 99%
“…It has long been established that PXR activation in hepatocytes can induce liver regeneration and even lead to hepatomegaly. PXR was specifically found to do this through an interaction with YAP [ 35 ]. Shizu et al (2013) also demonstrated this in a study which showed that PXR stimulation with PCN induced proliferation in liver cells.…”
Section: Pxr and Breast Cancermentioning
confidence: 99%